2020
DOI: 10.1097/ccm.0000000000004764
|View full text |Cite
|
Sign up to set email alerts
|

The Practice and Complications of Midline Catheters: A Systematic Review

Abstract: OBJECTIVE: Midline catheters are considered “midway” regarding vascular access. The objective of this systematic review was to explore the current practice, dwell time, and complication rates of midline catheters. DESIGN: Systematic review. SETTING: Search on four databases, PubMed, CINAHL, Scopus, and Embase, were conducted for English language articles published after the year 2000. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 42 publications
8
64
1
8
Order By: Relevance
“…Similarly, the complication rate was reported at 10.3% in a multicenter, prospective cohort study of aggregated data on 11 161 midline catheters from 12 hospitals 5. Furthermore, a systematic review of 31 articles including 6047 midline catheter insertions showed a similar failure rate of 12.5% 21. None of these studies controlled for catheter material.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the complication rate was reported at 10.3% in a multicenter, prospective cohort study of aggregated data on 11 161 midline catheters from 12 hospitals 5. Furthermore, a systematic review of 31 articles including 6047 midline catheter insertions showed a similar failure rate of 12.5% 21. None of these studies controlled for catheter material.…”
Section: Discussionmentioning
confidence: 97%
“…14,16,51 Unfortunately, MC-related research studies are often plagued with the limitations common to VAD-related research as a whole: retrospective analyses; single-site studies; small sample sizes; risk of bias; documentation gaps; and wide variability in research methods, VAD-related adverse event definitions, inclusion criteria, and VAD characteristics. 14,18,37,40,[53][54][55] The lack of high-quality VAD-related randomized controlled trials reduces the applicability of research recommendations to guide VAD selection and management. 6 The following paragraphs include examples of recent MC-related studies suggesting that MCs may be associated with a higher risk of adverse events than previously thought.…”
Section: Potential Risks Of Mcsmentioning
confidence: 99%
“…They acknowledged, however, that MC-related BSI rates are likely inaccurate because of inadequate surveillance. 18 In their prospective quality improvement program, Hankins et al 58 implemented a VAD selection algorithm that included an MC option and then monitored VADrelated outcomes. Although the MC-associated BSI rate was lower than the CLABSI rate during this initiative, they found significant correlations between MC dwell times and rates of BSI and thrombophlebitis, with an apparent increase in risk in patients who required multiple concurrent VADs.…”
Section: Potential Risks Of Mcsmentioning
confidence: 99%
“…Midline catheter programs are used by hospitals to avoid CLABSIs and associated financial penalties, an attractive benefit for any healthcare system [31]. Midline catheters can be associated with significantly fewer central line days, as well as significant cost savings (insertion of a midline being < $90), with multiple teams possibly being utilized for their placement (house staff, vascular access nurses, interventional radiology) [32][33][34].…”
Section: Alternative Cathetersmentioning
confidence: 99%